4x-2(-3x-7)=-10-6x

Simple and best practice solution for 4x-2(-3x-7)=-10-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2(-3x-7)=-10-6x equation:


Simplifying
4x + -2(-3x + -7) = -10 + -6x

Reorder the terms:
4x + -2(-7 + -3x) = -10 + -6x
4x + (-7 * -2 + -3x * -2) = -10 + -6x
4x + (14 + 6x) = -10 + -6x

Reorder the terms:
14 + 4x + 6x = -10 + -6x

Combine like terms: 4x + 6x = 10x
14 + 10x = -10 + -6x

Solving
14 + 10x = -10 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
14 + 10x + 6x = -10 + -6x + 6x

Combine like terms: 10x + 6x = 16x
14 + 16x = -10 + -6x + 6x

Combine like terms: -6x + 6x = 0
14 + 16x = -10 + 0
14 + 16x = -10

Add '-14' to each side of the equation.
14 + -14 + 16x = -10 + -14

Combine like terms: 14 + -14 = 0
0 + 16x = -10 + -14
16x = -10 + -14

Combine like terms: -10 + -14 = -24
16x = -24

Divide each side by '16'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| (a-5)=36 | | 10v^2-27v+5=0 | | -a/5=1/5 | | (x+3)(x+1)=4x+7 | | 2x^2+4x=621 | | t^2+4t+4=7 | | -5k=-14 | | 8x+3=4x+3 | | (u+1)*10=40 | | (q-10)*5=50 | | 5+3r=5 | | 2-2x/5=x-6 | | x^2+6x=120 | | 7x+3=19+5x | | 8y-2=14y-4 | | b=1/3=2 | | X^2+6x+33=0 | | (-4e^-2x)/(e^-5x) | | 16-3x=-7x+12 | | 5a^2-21a+18=0 | | 2/3a^2=23 | | 6x-10=-20 | | 14fa-72a^2+f^2= | | 2/3g=6=-12 | | -5z+6=6z-38 | | 144=-12(X+-60) | | a*bcd=bcd*a | | 1X+8=3X+14 | | (x+y)=3(x+y)-2 | | 4x-(3x-7)-(2x-3)=8x(x-1) | | 8z+4=11z-17 | | 3x+4(1)=-2 |

Equations solver categories